Development of Animated Video Learning Media to Improve Learning Outcomes in Senior High School Students at Rote Barat Laut 1 - Ledoh, Erlyn Marleni; Ersani, Erry; Samin, Mikael (Actual Insight, 2025)
Education is important for every generation, especially the younger generation. The use of learning media that utilizes available digital technology can be employed in education, such as animated media created with Canva. Canva can produce images and sounds as teaching aids, using the senses of sight and hearing in the process of absorbing learning material. The aim of this study is to determine the effect of animated video learning media with flora and fauna content on improving student learning outcomes at Rote Barat Laut 1 Senior High School. The method used in this study is Research and Development, which employs a research model consisting of the steps Analyze, Design, Development, Implementation, and Evaluation. The data collection instrument used is a test. The data analysis technique used is the independent t-test. The analysis results showed that the average pre-test score for the experimental class was 48.32 and the average post-test score was 86.2, while for the control class, the average pre-test score was 50.09 and the post-test score was 72.26. Based on calculations, the effect size (Cohen’s d) between the post-test scores of the experimental and control classes was 1.87. Therefore, it can be concluded that the development of animated video learning media with flora and fauna content significantly influenced the cognitive learning outcomes of students.